Playing evil. Role-playing games as an exploration of anti-etics - Thibault, Mattia (E|C, 2020)
The rules of role-playing games provide players with the tools to build possible coherent worlds, however fantastic, and characters that can move within them. The system of constraints that underlies each game limits the arbitrariness of the events that take place in the possible world, tying them to general rules and stable numerical values. Each player, then, will be able to "move" in this world by impersonating - and interpreting - a specific character whose role he will take in the story told by another player.